Quantitative Analysis of ?-Mangostin in Mangosteen Fruit Rind Extract (Deleted) (International Journal of Agricultural Research, Innovation and Technology, 2013)
The paper has been deleted due to plagiarismThe original paper is published in Thai Journal of Agricultural Science 2009, 42 (1): 7-12 (www.thaiagj.org)